Penerapan Pengendalian Proses Inventori Kontrol Pada Area Top Board - Tangguh Rajasa Ardhana; Rianita Puspa Sari (Jurnal Serambi Engineering, 2025)
This study examines how PT YM can improve the effectiveness of its inventory management by implementing the Just In Time (JIT) method. The main objective of the study is to overcome the problem of overstocking, which often occurs as a result of poor inventory management. Companies that use JIT produce items only in response to demand, which reduces inventory costs and storage requirements. According to the research, the implementation of JIT can increase production efficiency by 35% in an average of 11 days, with efficiency levels ranging from 27% to 38%. Moving average, linear trend and double exponential smoothing are some of the forecasting techniques used. Safety stock and kanban analysis are also used to ensure the best possible availability of raw materials. It is believed that the resulting recommendations will help with inventory management issues and serve as a guide for future inventory control studies.